Co-inhibition as a strategic therapeutic approach to overcome rifampin resistance in tuberculosis therapy: atomistic insights. (29th June 2018) - Agoni, Clement; Ramharack, Pritika; Soliman, Mahmoud ES
Aim: Amid the current global challenge of antimicrobial resistance, RNA polymerase remains a paramount therapeutic target for tuberculosis. Dual binding of rifampin (RIF) and a novel compound, DAAP1, demonstrated the suppression of RIF resistance. However, a paucity of data elucidating the structural mechanism of action of this synergistic interaction prevails.Methodology & results: Molecular dynamic simulations unraveled the synergistic inhibitory characteristics of DAAP1 and RIF. Co-binding induced a stable protein, increased the degree of compactness of binding site residues around RIF and subsequently an improved binding affinity toward RIF.Conclusion: Findings established the structural mechanism by which DAAP1 stabilizes Mycobacterium tuberculosis RNA polymerase, thus possibly suppressing RIF resistance. This study will assist toward the design of novel inhibitors combating drug resistance in tuberculosis.